Prediction analysis of the happiness ranking of countries based on macro level factors - Dini Oktarina Dwi Handayani; Muharman Lubis; Arif Ridho Lubis (IAES International Journal of Artificial Intelligence (IJ-AI), 2022)
Happiness is an essential universal human goal in their life that can improve the quality of life. Since the introduction of positive psychology, the primary consideration has been pointed out to the study of the role from certain factors in predicting the happiness, especially the advancement of technology that allows computer-mediated to be part of human interaction. It provides a multidimensional approach and indirect influence to the human expression and communication. The project investigates what it takes to build a happy country by analysing on the relationship between the happiness ranking of countries and their macro level factors. The World Happiness Report 2019 is used coupled with Python programming for visualizing and extracting information from the dataset to better understand the bigger picture.